SISTEM NUMERALIA BAHASA NGALUM - Siti Masitha Iribaram (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
One of the local language that found in the province of Papua with the largest number of speakers is Ngalum language. Ngalum language is spoken by Ngalum’s ethnic who lived in the Valley of  Oksibil, Okisop, and Okbon, Pegunungan Bintang Regency. One of the uniqueness of Ngalum language is numeralia system. Numeralia are words or phrases that show the number or quantity, can also to express the number of objects or their order in a row. This research uses descriptive method with three stages, namely providing data, data analysis, and  presentation of the results of data analysis. Data analysis was conducted after the data were  classified. The analysis that is applied using distributional method. Ngalum Language recognize five types of numeralia, namely numeralia principal, numeralia level, numeralia collective principal, principal numeralia indeterminate, and numeralia distributive. Numeralia of Ngalum is put in the front of phrase and the back of noun.